2014
DOI: 10.1111/bju.12796
|View full text |Cite
|
Sign up to set email alerts
|

Preferences in the management of high‐risk prostate cancer among urologists in Europe: results of a web‐based survey

Abstract: ObjectiveTo explore preferences in the management of patients with newly diagnosed high‐risk prostate cancer (PCa) among urologists in Europe through a web‐based survey.Materials and MethodsA web‐based survey was conducted between 15 August and 15 September 2013 by members of the Prostate Cancer Working Group of the Young Academic Urologists Working Party of the European Association of Urology (EAU). A specific, 29‐item multiple‐choice questionnaire covering the whole spectrum of diagnosis, staging and treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 28 publications
(30 reference statements)
0
14
0
2
Order By: Relevance
“…Several observational studies in men with regional nodal metastases have indicated a survival benefit for surgery, and current European Association of Urology (EAU) guidelines sanction surgery as an optional treatment for N1 prostate cancer in the context of multimodal therapy [19,20]. In fact, a recent survey of EAU members showed that two-thirds of practicing European urologists favor this approach [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies in men with regional nodal metastases have indicated a survival benefit for surgery, and current European Association of Urology (EAU) guidelines sanction surgery as an optional treatment for N1 prostate cancer in the context of multimodal therapy [19,20]. In fact, a recent survey of EAU members showed that two-thirds of practicing European urologists favor this approach [21].…”
Section: Discussionmentioning
confidence: 99%
“…34% (98) 14% (41) 12% (35) 19% (54) 21% (61) Sexual Function (n = 289) 57% (169) 12% (35) 11% (31) 15% (45) 5% (15) Hot Flushes (n = 295) 86% (238 ) 8% (23) 3% (8) 2% (7) 1% (2) Breast Tenderness (n = 278) 67% (192) 13% (37) 12% (34) 7% (19) 1% (3) Feeling Depressed (n = 285) 44% (132) 23% (68) 12% (34) 15% (45) 6% (18) Lack of Energy (n = 297) 63% (180) 11% (32) 12% (34) 9% (27) 5% (14) Body Weight (n = 287) (Table 4).…”
Section: Health Statusmentioning
confidence: 99%
“… (Table ). This multimodality approach is an often applied strategy for high‐risk patients in Europe .…”
Section: Discussionmentioning
confidence: 99%